ANALYSIS TOWARDS FACTORS THAT AFFECTING MILLENIALS’ ENTREPRENEURIAL INTENTION IN INDONESIA - Esti Riwayati, Hedwigis; Putri Liberty, Angela Natasya; Rizki Noviah, Nyi Mas (Dinasti International Journal of Digital Business Management, 2021)
This research aims to analyze those factors which have an impact towards the entrepreneurial intention on millennial business people in DKI Jakarta. This research was conducted on millennial Micro, Small and Medium Enterprises in DKI Jakarta. The Sampling was taken by a purposive sampling technique. Then the research data obtained by distributing questionnaires to 400 respondents. The data analysis technique that used was multiple linear regression analysis which processed through SPSS 25. The Summary results showed that entrepreneurial motivation, personality and family environment had a significant positive impact on their entrepreneurial intention. While Entrepreneurial knowledge does not have any impact towards entrepreneurial intention on millennial business people in DKI Jakarta. Entrepreneurial motivation, personality, entrepreneurial knowledge and family environment are suitable to explain further relates to the topic.